2021
DOI: 10.1021/acs.jpcc.0c09009
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Insights into the Tunable Luminescence of CuAlxFe1–xS2/ZnS Nanocrystals

Abstract: We describe the electronic structure and spectroscopic properties of CuAl x Fe1–x S2 nanocrystals and their core/shell structures. The as-synthesized CuAl x Fe1–x S2 core exhibits a tetragonal chalcopyrite structure. The core material exhibits tunable band gap that spans the entire visible to near-infrared spectrum, from 3.48 to 0.53 eV. This tunability is achieved by varying the mole fraction of aluminum and iron from 1:0 to 0:1. The band gap variation with composition deviates from Vegard’s law and correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…For example, CuFeS x Se 2− x NCs have an SPR band at 408 nm (Figure 3e) [ 66 ] and CuAl x Fe 1− x S 2 at 480 nm (Figure 3f). [ 67 ] Further studies also indicate that the plasmon in these materials is quite stable and inert to different stoichiometric changes in the NCs. Very recently, Cu 3 VS 4 (sulvanite) NCs have shown similar but multiple SPR bands in the visible range.…”
Section: Optical Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, CuFeS x Se 2− x NCs have an SPR band at 408 nm (Figure 3e) [ 66 ] and CuAl x Fe 1− x S 2 at 480 nm (Figure 3f). [ 67 ] Further studies also indicate that the plasmon in these materials is quite stable and inert to different stoichiometric changes in the NCs. Very recently, Cu 3 VS 4 (sulvanite) NCs have shown similar but multiple SPR bands in the visible range.…”
Section: Optical Propertiesmentioning
confidence: 96%
“…f) Absorption spectra of CuAl x Fe 1−x S 2 nanoparticles versus the Al/Fe ratios. Reproduced with permission [67]. Copyright 2016, American Chemical Society.…”
mentioning
confidence: 99%
“…Besides the success of colloidal approaches to CuFeS 2 NC synthesis, researchers have also successfully employed milling and microwave to produce CuFeS 2 NCs. , In particular, Kumar et al were able to demonstrate NIR photodetection in microwave CuFeS 2 NC/ZnO oxide hybrids . Other iron-based I–III–VI 2 NCs such as CuFeSe 2 NCs also demonstrate a similar set of optical and optoelectronic properties. The availability of a wide library of I–III–VI 2 semiconductors with narrow band gaps and a well-defined composition could in principle reduce the reliance on alloying and quantum confinement based strategies that need to be pursued in the case of HgTe-based materials. Phototdetector devices directly relying on sintered I–III–VI 2 inks could thus present significant advantages in the future.…”
Section: Applications Of I–iii–vi2 Nanocrystalsmentioning
confidence: 99%
“…Recently, Yadav et al demonstrated the ability to synthesise quaternary earth-abundant CuAl x Fe 1−x S 2 nanocrystals with a band gap that is tunable across the entire UV/vis/NIR spectrum, whilst maintaining the chalcopyrite crystal structure [45]. As part of this work, they performed a limited DFT investigation into the electronic structure of the CuAl x Fe 1−x S 2 system showing the projected density of states (PDOS) calculated for the CuAl 0.75 Fe 0.25 S 2 system, the composition of which was obtained by substituting two Al 3+ ions with Fe 3+ ions, i.e., by introducing two [Fe Al ] 0 antisite defects.…”
Section: Introductionmentioning
confidence: 99%